Neonatal Irradiation Sensitizes Mice to Delayed Pulmonary Challenge - Johnston, Carl J. (2012)
Significant differences exist between the physiology of the immature, neonatal lung compared to that of the adult lung that may affect acute and late responses to irradiation. Identifying these differences is critical to developing successful mitigation strategies for this special population. Our current hypothesis proposes that irradiation during the neonatal period will alter developmental processes, resulting in long-term consequences, including altered susceptibility to challenge with respiratory pathogens. C57BL/6J mice, 4 days of age, received 5 Gy whole-body irradiation. At subsequent time points (12, 26 and 46 weeks postirradiation), mice were intranasally infected with 120 HAU of influenza A virus. Fourteen days later, mice were sacrificed and tissues were collected for examination. Morbidity was monitored following changes in body weight and survival. The magnitude of the pulmonary response was determined by bronchoalveolar lavage, histological examination and gene expression of epithelial and inflammatory markers. Viral clearance was assessed 7 days post-influenza infection. Following influenza infection, irradiated animals that were infected at 26 and 46 weeks postirradiation lost significantly more weight and demonstrated reduced survival compared with those infected at 12 weeks postirradiation, with the greatest deleterious effect seen at the late time point. The results of these experiments suggest that radiation injury during early life may affect the lung’s response to a subsequent pathogenic aerial challenge, possibly through a chronic and progressive defect in the immune system. This finding may have implications for the development of countermeasures in the context of systemic radiation exposure.